Green Energy Process "Ozonation" and Food Safety: A Comprehensive Review. - ISLAM, FAKHAR; IMRAN, ALI; KHALID, MUHAMMAD ARMGHAN; AFZAAL, MUHAMMAD; FATIMA, MALEEHA; CHAUHAN, ANAMIKA; BISWAS, SUNANDA; ZAHRA, SYEDA MAHVISH; SHEHZADI, UMBER; ATEEQ, HUDA; SHAH, MOHD ASIF; OJUKWU, MOSES (Current Research in Nutrition & Food Science, 2023)
Improving the storage life of food products is a major problem for manufacturers, and the food sector needs an "ecofriendly" alternative to present technology. As a disinfectant, ozone has been utilized in waste-water purification systems since the beginning of the century. Recently, ozone has been utilized to handle a wide variety of agricultural products because of its qualities, including fast disintegration and low residual consequences during food preservation. Ozone is an interesting substitute preservative that the food industry demands and a suitable decontaminator for guaranteeing the microbiological hygiene and safety of food products. Ozone treatment has been demonstrated to be a potential strategy for lowering pollutants in dairy effluents. This review comprehensively highlights ozonation as a preservative in dairy, fruits and vegetables, poultry, cereals, and fresh produce in depth for save and effective use of ozone, whereas other published articles only discuss one of these categories. Overall, ozone has proven to be a viable technique, despite its high food-preservation efficacy, and market certification requires extensive information on the applicability of ozone-based technologies and their potential benefits.